Over 14% Efficiency in Organic Solar Cells Enabled by Chlorinated Nonfullerene Small‐Molecule Acceptors. Issue 28 (28th May 2018) - Zhang, Hao; Yao, Huifeng; Hou, Junxian; Zhu, Jie; Zhang, Jianqi; Li, Wanning; Yu, Runnan; Gao, Bowei; Zhang, Shaoqing; Hou, Jianhui
Abstract: To make organic solar cells (OSCs) more competitive in the diverse photovoltaic cell technologies, it is very important to demonstrate that OSCs can achieve very good efficiencies and that their cost can be reduced. Here, a pair of nonfullerene small‐molecule acceptors, IT‐2Cl and IT‐4Cl, is designed and synthesized by introducing easy‐synthesis chlorine substituents onto the indacenodithieno[3, 2‐ b ]thiophene units. The unique feature of the large dipole moment of the CCl bond enhances the intermolecular charge‐transfer effect between the donor–acceptor structures, and thus expands the absorption and down shifts the molecular energy levels. Meanwhile, the introduction of CCl also causes more pronounced molecular stacking, which also helps to expand the absorption spectrum. Both of the designed OSCs devices based on two acceptors can deliver a power conversion efficiency (PCE) greater than 13% when blended with a polymer donor with a low‐lying highest occupied molecular orbital level. In addition, since IT‐2Cl and IT‐4Cl have very good compatibility, a ternary OSC device integrating these two acceptors is also fabricated and obtains a PCE greater than 14%. Chlorination demonstrates effective ability in enhancing the device performance and facile synthesis route, which both deserve further exploitation in the modification of photovoltaic materials. Abstract : A pair of nonfullerene small‐molecule acceptors, IT‐2Cl and IT‐4Cl, is designed and synthesized by easy‐synthesis chlorine substituents. The CCl bond enhances the intermolecular charge‐transfer effect between the donor–acceptor structures and molecular structure order. Both binary devices show efficiency beyond 13%, and a ternary organic solar cell device integrating these two acceptors obtains an efficiency greater than 14%.